VD_FINDINFO HC / 2013 / 488 vom 23. August 2013 - VD Tribunal cantonal (2013)
PROTECTION DE L'UNION CONJUGALE, MODIFICATION DES CIRCONSTANCES, OBLIGATION D'ENTRETIEN | 163 CC, 176 al. 1 ch. 1 CC, 179 CC, 276 CPC (CH), 317 al. 1 CPC (CH)